A new method for extracting seismic indices and granulation parameters: Results for more than 20, 000 CoRoT and Kepler red giants. Issue 2 (28th May 2018) - de Assis Peralta, R.; Samadi, R.; Michel, E.
Abstract : We have developed a new automated method intended to perform the simultaneous—and thus more consistent—measurement of both the seismic indices characterizing the oscillations and the parameters characterizing the granulation signature of red giant stars. This method, called MLEUP, takes advantage of the Maximum Likelihood Estimate (MLE) algorithm combined with the parameterized representation of red giant pulsation spectra following the universal pattern (UP). Its performances have been tested on Monte Carlo simulations for observation conditions representative of CoRoT and Kepler data. These simulations allowed us to determine, calibrate, and propose corrections for the biases on the parameter estimates as well as on the error estimates produced with MLEUP. Finally, we applied MLEUP to CoRoT and Kepler data. In total, MLEUP yields seismic indices for 20, 122 red giant stars and granulation parameters for 17, 109 of them. These data have been made available in the stellar seismic indices database (http://ssi.lesia.obspm.fr /).